Mad tales from the Raj colonial psychiatry in South Asia, 1800-58 - Ernst, Waltraud, 1955- (Anthem South Asian studies., 2010)
"Mad Tales from the Raj: Colonial Psychiatry in South Asia, 1800-58 is an authoritative assessment of western psychiatry within the context of British colonialism. This updated version provides a comprehensive study of official attitudes and practices in relation to both Indian and European patients during the dominance of the British East India Company. It includes a fully revised introduction that locates the work in relation to recent scholarly discourse in the field of history of colonial medicine. Based on government proceedings, medical case reports, contemporary publications, diaries and literary material, Mad Tales from the Raj provides a highly readable and illuminating account of contemporary psychiatric treatment and colonial policies. It is fascinating reading not only to students of colonial history, medical sociology and related disciplines, but to all those with a general interest in life in the colonies."--Publisher's description.